Women's Empowerment (Case Study on Tanah Liek Batik Group) in Teluk Sikai, Sungai Duo Dharmasraya - Agi Brillianti, Nur; Dasa Putri, Lili (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research was conducted to find out that empowerment in a society is very important to advance people's welfare. Most people in Indonesia have their own creativity which is very productive, they just don't realize it. Empowerment is one of the first steps in community activities to improve welfare towards the survival of the community. Women's empowerment is carried out in order to grow the strengths of women so that they are able to develop and prosper, one of which is through the Tanah Liek batik group in Jorong, Sikai Bay, Duo Dharmasraya River. It is very visible that the existence of this batik group can improve the community's economy and create jobs. for people who work as housewives only. This research aims (1) To determine the implementation of learning between fellow craftsmen. (2) To determine the community's environmental support for the Tanah Liek Batik Group. (3) To find out the impact obtained by the Tanah Liek Batik Group craftsmen.This research uses a qualitative approach with the nature of a case study which aims to provide an overview of the findings. The location of this research is Jorong Teluk Sikai, Nagari Sungai Duo, Sitiung District, Dharmasraya Regency. The sources for this research are managers, women who work in the Tanah Liek batik group who can be interviewed, village heads and the surrounding community. The data collection techniques used in this research are interviews, observation and documentation. The validity of the data obtained from this research is based on source triangulation, method triangulation, and theory triangulation.The results of the research show that: (1) There is an implementation of learning between fellow craftsmen in the form of cooperation and giving each other advice, (2) There is support from the surrounding environment for the Tanah Liek batik group physically and non-physically, namely women's empowerment in Sikai Bay, (3) Impact What the craftsmen in the Tanah Liek Batik Group get is able to provide employment opportunities for mothers who only work as housewives, and can help improve the family economy of the craftsmen in the Tanah Liek Batik group.Keywords: Women's Empowerment, Tanah Liek Batik